MINAT MELANJUTKAN STUDI KE PERGURUAN TINGGI SISWA TATA BUSANA SEKOLAH MENENGAH KEJURUAN YOGYAKARTA MINAT MELANJUTKAN STUDI KE PERGURUAN TINGGI SISWA KELAS XII TATA BUSANA SEKOLAH MENENGAH KEJURUAN MA’ARIF AL-MUNAWWIR YOGYAKARTA - marisa, irawati (Universitas Sarjanawiyata Tamansiswa, 2025)
The purpose of this study was to determine the interest in continuing their studies to tertiary institutions for class XII students of Fashion Design at SMK Ma'arif Al-Munawwir Yogyakarta, seen from internal factors and external factors. This research is a type of quantitative descriptive research. Methods of data collection using questionnaires and documentation. Data analysis techniques use descriptive analysis techniques to calculate the Mean, Median, Mode, and Standard Deviation. The results showed that the interest in continuing their studies to tertiary institutions for class XII students of Fashion Design at Ma'arif Al-Munawwir Vocational High School Yogyakarta was in the sufficient category with a relative frequency of 58.33%. Variable students' interest in continuing their studies at tertiary institutions has two indicators, namely internal factors and external factors. Internal factors are a sufficient category with a relative frequency of 65% and external factors are in the sufficient category with a relative frequency of 50%. Keywords: interest, fashion, study at university